The future of preconception care in the United States: multigenerational impact on reproductive outcomes. (1st October 2016) - St. Fleur, Michelle; Damus, Karla; Jack, Brian
Abstract: The future of preconception care will require an innovative multigenerational approach to health promotion for women and men to achieve optimal reproductive health outcomes. In this paper we provide a summary of historical trends in perinatal interventions in the United States that have effectively reduced adverse perinatal outcomes but have not improved disparities among ethnic/racial groups. We describe evidence pointing to an enhanced preconception care paradigm that spans the time periods before, during, and between pregnancies and across generations for all women and men. We describe how the weathering, Barker, and life course theories point to stress and non-chromosomal inheritance as key mediators in racial disparities. Finally, we provide evidence that indicates that humans exposed to toxic stress can be impacted in future generations and that these phenomena are potentially related to epigenetic inheritance, resulting in perinatal disparities. We believe that this expanded view will define preconception care as a critical area for research in the years ahead.